2012
DOI: 10.1523/jneurosci.5757-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-Selective Allosteric Inhibition of Glycine Binding to NMDA Receptors

Abstract: NMDA receptors are ligand-gated ion channels that mediate excitatory neurotransmission in the brain, and are involved in numerous neuropathological conditions. NMDA receptors are activated upon simultaneous binding of co-agonists glycine and glutamate to the GluN1 and GluN2 subunits, respectively. Subunit-selective modulation of NMDA receptor function by ligand binding to modulatory sites distinct from the agonist binding sites could allow pharmacological intervention with therapeutically beneficial mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 46 publications
8
121
0
Order By: Relevance
“…1) and is critical for glycine-dependent inhibition by and N-(cyclohexylmethyl)-2-({5-[(phenylmethyl)amino]-1,3,4-thiadiazol-2-yl}thio)acetamide (TCN-213) (Hansen et al, 2012;McKay et al, 2012). Given the role of the ABD dimer interface in mediating allosteric coupling between the ATD and the ion channel gate (Gielen et al, 2008(Gielen et al, , 2009, and the importance of the ABD dimer interface of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors for the activity of positive modulators such as cyclothiazide (Sun et al, 2002), we asked whether the ABD dimer interface of NMDA receptors might contribute to potentiation by CIQ.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations
“…1) and is critical for glycine-dependent inhibition by and N-(cyclohexylmethyl)-2-({5-[(phenylmethyl)amino]-1,3,4-thiadiazol-2-yl}thio)acetamide (TCN-213) (Hansen et al, 2012;McKay et al, 2012). Given the role of the ABD dimer interface in mediating allosteric coupling between the ATD and the ion channel gate (Gielen et al, 2008(Gielen et al, , 2009, and the importance of the ABD dimer interface of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors for the activity of positive modulators such as cyclothiazide (Sun et al, 2002), we asked whether the ABD dimer interface of NMDA receptors might contribute to potentiation by CIQ.…”
Section: +mentioning
confidence: 99%
“…Given the role of the ABD dimer interface in mediating allosteric coupling between the ATD and the ion channel gate (Gielen et al, 2008(Gielen et al, , 2009, and the importance of the ABD dimer interface of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors for the activity of positive modulators such as cyclothiazide (Sun et al, 2002), we asked whether the ABD dimer interface of NMDA receptors might contribute to potentiation by CIQ. Two residues in GluN1 contributing to the dimer interface, Phe754 and Arg755, were critical for inhibition of GluN1/GluN2A receptors by TCN-201 (Hansen et al, 2012), and mutation of these residues to alanine altered the binding of TCN-201. By contrast, CIQ potentiation was…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Because TCN 201 is reported to be a negative allostereic modulator of glycine binding in GluN1/2A receptors (Edman et al, 2012;Hansen et al, 2012), we examined it in the presence of bitopertin, a glycine uptake inhibitor. It has been reported that 100 nM, but not 300 nM, bitopertin facilitates LTP induction in rat slices (Alberati et al, 2012).…”
Section: Resultsmentioning
confidence: 99%